Ion Exchange Properties of Resins Derived from p-Hydroxybenzaldehyde, Resorcinol and Formaldehyde - V. V. Hiwase; A. B. Kalambe; K. M. Khedkar; S. D. Deosarkar (E-Journal of Chemistry)
The terpolymeric resins were prepared by base catalyzed polycondensation of p-hydroxybenzaldehyde, resorcinol and formaldehyde. Resin obtained by molar monomer composition, p-hydroxybenzaldehyde: resorcinol: formaldehyde as 1:1:3 was abbreviated as PHBRF-I and that prepared by 1:2:4 composition was abbreviated as PHBRF-II. These resins were characterized by physicochemical methods such as elemental analysis, UV-Vis, IR and NMR. ion-exchange study was carried out with Cu2+, Zn2+, Ni2+, Co2+, Pb2+ & Cd2+ by batch equilibrium method. The rate of metal ion uptake by PHBRF-II terpolymeric resin was higher than that of PHBRF-I. Effect of pH and electrolytes under specified condition were also studied. The terpolymeric resins show high selectivity for Cu2+, Zn2+ and Co2+ as compared to Ni2+, Pb2+, and Cd2+.